Motivated students motivating students: Sustainable Development Goals: a sensitization initiative - Menacho, Carmen; Felipe-Andreu, Javier (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Young people are concerned about unsustainability; however, they distance themselves from pro-sustainable attitudes due to considering that individual acts have no effect. For this reason, an initiative led by young student volunteers in pursuit of sustainability was developed. The methodology for the creation, development and evaluation of the initiative is presented. It was based on creating spaces for reflection, discussion, self-criticism, and motivation. Results showed a real impact on the students’ individual behaviour: 82% was motivated to make a change and 65% changed some habits. In addition, initiatives and collaborations emerged between attendees and speakers seeking to transform society.